نمذجة البنائية والسلوكية لنظام توليد نبضات PWM اعتماداً على لغة النمذجة VHDL_AMS - محمد, نبال (Latakia University Journal -Engineering Sciences Series, 2019)
In this work we have modeling and simulation of system generation of (PWM), in order to do this, taking into account the plurality terms reference of model (Electricity, electron, mechanics, heat, magnetism, light, etc.), and contain on the analog and digital signals, was to be of use one of high level modeling languages as (HDL), and where is the VHDL_AMS language the most important and the most commonly used by the major industrial companies international because it is able to description of the system within environment simulation one. In the first phase: we model each element of the elements of the circuit separately and testing it, then connect the elements together, then test the circuit make a simulation using a tool for simulation( simplorer). In the second phase: we model the general behavior of the system directly and test of the behavioral model make a simulation using a tool for simulation( simplorer), then we compare the results of tests stating the importance of behavioral modeling. تم في هذا العمل نمذجة ومحاكاة نظام توليد نبضات PWM، ومن أجل القيام بعملية النمذجة تم الأخذ بعين الاعتبار تعددية اختصاصات النموذج (كهرباء، إلكترون، مكانيك، حرارة، مغناطيسية، ضوء، ... الخ.) واحتوائه على إشارات رقمية وتماثلية كان لابد من استخدام إحدى لغات النمذجة العالية المستوى مثل لغات Hardware Description Language (HDL) حيث تعتبر لغة الـ VHDL-AMS أهمها وأكثرها استخداماً من قبل كبرى الشركات الصناعية العالمية لأنها قادرة على وصف كامل النظام ضمن بيئة محاكاة واحدة. تم في البداية نمذجة كل عنصر من عناصر النظام على حده ثم وصل العناصر معا واختبار النظام بإجراء عملية المحاكاة مستخدمين أداة المحاكاة Simplorer، ثم تم نمذجة السلوك العام لدارة PWM مباشرةً واختبار النموذج السلوكي ومقارنة نتائج الاختبارين، موضحين أهمية النمذجة السلوكية.